Adverse human health effects of climate change: an update - Filippini, Tommaso; Paduano, Stefania; Veneri, Federica; Barbolini, Giulia; Fiore, Gianluca; Vinceti, Marco (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. The world is currently facing a process of climate change, which may adversely impact human health in many different ways. The safety of food, water and urban environments is endangered by the consequences of climate change. Sea level and temperature rise, along with more frequent and longer heat waves, represent only a few of the effects of climate change. The increased risk of extreme climate events (e.g., cyclones, droughts and floods) is another serious public health issue. These adverse effects are enhanced in areas and countries not having the capacity to effectively deal with climate change. Study design. We primarily aimed at summarizing the impacts of climate change on public health. A further aim was to identify the most concerning consequences of this phenomenon and the vulnerability factors that amplify the negative effects of climate change. Methods. PubMed and other literature databases were used as literature sources for this narrative review based on the search terms ‘climate change’ and ‘diseases categories’ up to January 2024, in order to assess the most recent and relevant scientific evidence about the relation between climate change and public health, identify knowledge gaps and priorities for future research. We also screened the websites of major agencies devoted to human health protection and environmental health. Results and Conclusions. Climate change appears to induce a broad spectrum of generally adverse effects on public health. It may increase the risk of infectious diseases, psychiatric disorders, cancer and other diseases. Currently, we are not effectively counteracting this phenomenon, since pollutant and greenhouse gas emissions have been increasing alongside temperatures. A host of measures are required in order to prevent and fight climate change and related health effects. These include the adoption of a holistic approach and the collaboration of different kinds of expertise in order to design more effective strategies. Special attention should be paid to those who live in disadvantaged countries, and those who are more vulnerable to the adverse health consequences of climate change.